A water-soluble supramolecular polymeric dual sensor for temperature and pH with an associated direct visible readout. (August 2015) - Malfait, Aurélie; Coumes, Fanny; Fournier, David; Cooke, Graeme; Woisel, Patrice
Graphical abstract: Highlights: Synthesis of a multi-stimuli responsive diaminonaphthalene functionalized PNIPAM. Elaboration of a water-soluble host-guest supramolecular polymeric dual sensor. The pseudorotaxane polymer architecture can be reversibly dissociated on demand. Abstract: We report a multi-stimuli responsive polymeric sensor consisting of a pseudorotaxane-like architecture fabricated from a 1, 5-diaminonaphthalene end-functionalized poly( N -isopropyl)acrylamide (Napht-N-PNIPAM ) and cyclobis(paraquat- p -phenylene) (CBPQT 4 +, 4Cl − ). The coloured nature of the poly-pseudorotaxane provides a sensor for temperature and pH in water with an associated visible readout. To create this dual responsive polymeric sensor, a new chain transfer agent (Napht-N-CTA ) incorporating a pH-responsive 1, 5-diaminonaphthalene unit was synthesized and used for the polymerization of N -isopropylacrylamide via Reversible Addition-Fragmentation Chain Transfer (RAFT). The ability ofNapht-N-PNIPAM to form a pseudorotaxane architecture withCBPQT 4 +, 4Cl − in aqueous media was studied by means of UV–Vis, NMR ( 1 H, 2D-ROESY, DOSY) and ITC experiments. Interestingly, the pseudorotaxane architecture can be reversibly dissociated upon either heating the sample above its cloud point or protonating the nitrogen atoms of the 1, 5-diaminonaphthalene-based guest unit by adjusting the pH to around 1. In both cases a dramatic colour change occurs from intense blue-green to colourless.